2D Nanocrystals: SMART Design of a Bulk‐Capped Supramolecular Segment for the Assembly into Organic Interdigital Lipid Bilayer‐Like (ILB) Nanosheets (Small 6/2018). Issue 6 (8th February 2018) - Li, Yin‐Xiang; Wang, Sha‐Sha; Yu, Yang; Zhang, He; Wang, Wu‐You; Yang, Ru‐Qian; Xie, Ling‐Hai; Liu, Feng; Lin, Zong‐Qiong; Shi, Nai‐En; Sun, Li‐Tao; Huang, Wei
Abstract : In article number 1703151, Ling‐Hai Xie, Li‐Tao Sun, Wei Huang, and co‐workers propose a general strategy for programmable 2D organic nanosheets formation based on the synergistically molecular attractor‐repulsor theory (SMART). As a typical attractor‐repulsor model molecule, TPA‐PF is made up of a supramolecular segment TPA and a bulky group PF. The synergetic effect between them leads to an interdigital lipid bilayer‐like (ILB) molecular packing mode and 2D organic nanosheets.